PENDIDIKAN KARAKTER BERBANTUAN MATERI SEJARAH LOKAL DI SMA NEGERI 3 PONTIANAK - Bakti, Yunita; Noor, Agus Sastrawan; Firmansyah, Andang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe motivated of this research is based on the interest of researcher for SMA Negeri 3 Pontianak which the winner of Olimpiade Pahlawan Indonesia (OPI) at Pontianak in 2016. The researcher be interested and want to know how the teacher of the history subject at SMA Negeri 3 Pontianak to deliver Indonesian local history. The purpose of this research is to know how the teacher prepare before present material, the building of character values in student, and what are the supporting and obstacle factor. In present this local history method was applied in this research were qualitative approach with the from of case study research, the research applied observation technique, deep interview, and documents study. The tool of collecting data is consist of the interview guide, observation sheet, and documents. Based the result of research shows that local history material is inserted between Indonesian historical material, in the delivery of the teacher?s local history material using brainstorming methods, students are very excited in following the learning process. Supporting factors here are both projector and speakers the are commonly used in the learning process, the obstacle factor in the delivery of local history material is the history material has not been incorporated into the national curriculum and it is difficult to find valid sources or material. Keywords: Characters Building, History Learning, Local History Material